Kajian Eko Interior Pada Hotel Budget di Balikpapan - Chelline Monica Gani (Intra, 2016)
Ecological approach in the planning and building design requirements that should be met by the perpetrators of physical development. Hotel is one example of a physical building. Now, the hotel concept